Citizen Engagement : Emerging Digital Technologies Create New Risks and Value - Peixoto, Tiago (World Bank, Washington, DC, 2019)
The recent rapid evolution of digital technologies has been changing behaviors and expectations in countries around the world. These shifts make it the right time to pose the key question this paper explores: Will digital technologies, both those that are already widespread and those that are still emerging, have substantial impacts on the way citizens engage and the ways through which power is sought, used, or contested? The authors address this question both to mitigate some of the World Bank’s operational risks, and to initiate a conversation with peers about how those risks might require policy shifts. The overall framing question also is being explored in case theapproaches to citizen engagement advocated by the World Bank are changing and may require different advice for client countries. Despite the lower technology penetration levels in developing countries, their more malleable governance contexts may be more influenced by the effects of emerging technologies than older states with greater rigidity. Digitally influencedcitizen engagement is, in short, one of those “leapfrog” areas in which developing nations may exploit technologies before the wealthier parts of the world. But countries can leapfrog to worse futures, not just better ones. This paper explores what technology might mean for engagement, makespredictions, and offers measures for governments to consider.